2019
DOI: 10.2196/12639
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Implementation, User Perspectives, and Feedback From a Mobile Health Intervention for Individuals Living With Hypertension (DREAM-GLOBAL): Mixed Methods Study

Abstract: BackgroundDREAM-GLOBAL (Diagnosing hypertension—Engaging Action and Management in Getting Lower Blood Pressure in Indigenous and low- and middle-income countries) studied a SMS text messaging–based system for blood pressure measurement and hypertension management in Canadian Aboriginal and Tanzanian communities. The use of SMS text messages is an emerging point of interest in global health care initiatives because of their scalability, customizability, transferability, and cost-effectiveness.ObjectiveThe study… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 16 publications
1
25
0
Order By: Relevance
“…Patients can now access personal health information through patient portals [6], look up health information independently without professional medical guidance [7][8][9][10][11], and provide feedback to other consumers on their experiences with certain hospitals or providers through these media [12]. Studies have shown that the use of technology in the health sector can improve intervention efficacy, patient satisfaction, and, ultimately, clinical outcomes [13][14][15][16][17]. Technology has assumed a growing role within the health care landscape, with more than 60% of all US health care institutions using at least one form of telehealth [18], with some engaging in more telehealth visits than in-person visits [19].…”
Section: Introduction Backgroundmentioning
confidence: 99%
“…Patients can now access personal health information through patient portals [6], look up health information independently without professional medical guidance [7][8][9][10][11], and provide feedback to other consumers on their experiences with certain hospitals or providers through these media [12]. Studies have shown that the use of technology in the health sector can improve intervention efficacy, patient satisfaction, and, ultimately, clinical outcomes [13][14][15][16][17]. Technology has assumed a growing role within the health care landscape, with more than 60% of all US health care institutions using at least one form of telehealth [18], with some engaging in more telehealth visits than in-person visits [19].…”
Section: Introduction Backgroundmentioning
confidence: 99%
“…Despite the lack of inclusion of Indigenous communities early in product development by technology producers and creators, Indigenous communities have not sat idly by but have instead embraced mobile technology in unique and creative ways. 3 As indicated earlier, there are several examples of quality research programs using community-based, culturally safe approaches to technology development, 18,61,62 though there remains severe limitations in studies conducted within the area of dementia care for Indigenous communities. Although generalizing from one Indigenous community to another is fraught with problems, the current results show that caregivers of persons with dementia and professionals are eager to participate in technology development, they provide unique problems for industry to solve, and using their local knowledge of dementia care within the culture, they can provide potential solutions that will enhance eventual marketability of wearable technology for dementia care.…”
Section: Discussionmentioning
confidence: 99%
“…Within mHealth technologies a handful of products have been developed within Indigenous or American Indian communities using community-based participatory research (CBPR) methodologies including breastfeeding, medication adherence, alcohol consumption during pregnancy, hypertension, and general healthy lifestyle support. 14 20 While these are notably important health priorities, none of these medical conditions are related to dementia and aging-in-place. The general exploration of mHealth or eHealth applications among adults supports the feasibility and indicates a general interest in technologies, though economic and connectivity limitations in rural and remote areas are always a strong concern.…”
Section: Introductionmentioning
confidence: 99%
“…Automated texting in particular has been leveraged nationally and globally for remote hypertension management, with high patient engagement and satisfaction among low-income and underserved populations [ 7 , 8 ]. Automated texting interventions can double the odds of medication adherence for chronic conditions, regardless of whether texts are unidirectional or interactive [ 9 ].…”
Section: Introductionmentioning
confidence: 99%